2021
DOI: 10.2147/imcrj.s306558
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Assistive Limb Functional Treatment for a Patient with Chronic Incomplete Cervical Spinal Cord Injury

Abstract: Introduction The hybrid assistive limb (HAL) is a wearable exoskeleton cyborg that assists walking and lower limb movements via real-time actuator control by detecting the wearer’s bioelectric signals on the surface of their skin. Purpose The purpose of this study was to report the improvement in walking ability following HAL gait training in a patient with tetraplegia after incomplete cervical spinal cord injury (SCI). Patient and Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In another word, HAL technology utilises intention to make movements to precisely control exoskeletons and reproduce intended movements, known to enhance motor control functions and improve neurological disorders [53,54]. Ankle-HAL technology was developed for rehabilitation to focus on joint motion training by users' own neuro-signals, therefore not designed to directly assist active walking [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…In another word, HAL technology utilises intention to make movements to precisely control exoskeletons and reproduce intended movements, known to enhance motor control functions and improve neurological disorders [53,54]. Ankle-HAL technology was developed for rehabilitation to focus on joint motion training by users' own neuro-signals, therefore not designed to directly assist active walking [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for gait training using HAL to improve the ability of patients with chronic severe incomplete tetraplegic SCI to walk was also shown. HAL motion-assistive technologies contributed to improvement in patient walking ability by facilitating proper joint motion and loading and unloading muscle movements (Soma et al, 2021).…”
Section: Rehabilitation Approaches For Chronic Spinal Cord Injurymentioning
confidence: 99%
“…There are various versions of HALs, such as a double-leg version 7) , single-leg version 8) , single-joint version (for a shoulder, elbow, or knee) [9][10][11] , and a version for hips 12) . Indeed, previous studies showed the benefits of HAL gait training in cases of spinal cord injury 13) , acute and chronic myelopathy 7,14,15) , spinal dural arteriovenous fistula 16) , and spinal cord infarction 17) . However, there have been no reports on the use of the ankle HAL in cases of peroneal nerve palsy, and its effectiveness in this regard has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%